UPAYA MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN PUZZLE MEDIA SISWA SDN 1 MIMBAAN SITUBONDO - Sumardiyanto; Dassucik; Rahman, Fathor (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study examines the impact of using puzzle media in math learning on student learning outcomes at SDN 1 Mimbaan, Indonesia. The study aimed to improve students' understanding and motivation in math by applying an interactive and fun learning tool. A classroom action research method with two cycles was conducted, involving 28 grade II students. The study focused on addition and subtraction materials, using puzzle media to promote student engagement. Pre-action test results showed that 86% of students had not reached the minimum completeness criteria. However, after implementing the puzzle media, the results improved significantly in Cycle I, where 64% of students reached the completeness target. In Cycle II, 93% of students achieved completeness, exceeding the expected target. The study concluded that puzzle media effectively improved students' understanding and motivation in mathematics, making learning more interactive and fun. The research recommends the integration of puzzle media in the learning process to improve learning outcomes and student engagement in basic education.